Cryptography With McEliece Algorithm (Code Based Cryptography) - Priska Gultom; Melita Sidauruk; Arlan Lombu; Histori Mei Selamat Gulo (Jurnal Teknik Indonesia, 2023)
The McEliece algorithm is one of the code-based cryptography methods that offers a high level of security, especially against quantum computing threats. This algorithm uses error-correcting codes to encrypt messages, making them difficult to crack by conventional cryptanalysis attacks. This study analyzes the implementation of the McEliece algorithm through manual calculations and simulations using the Python programming language. The results of the analysis show that this algorithm has a strong encryption mechanism, with the key formation, encryption, and decryption processes running according to theory. In addition, the use of error-correcting codes has proven effective in repairing messages that are disrupted during transmission. The program implementation shows that McEliece can be applied in real scenarios with a high level of accuracy. With these advantages, the McEliece algorithm is a strong candidate for post-quantum security systems.